Reduction of Radiation Dose and Scanning Time While Preserving Diagnostic Yield: A Comparison of Battery-Powered and Manual Bone Biopsy Systems - Kihira, S.; Koo, C.; Lee, A.; Aggarwal, A.; Pawha, P.; Doshi, A. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: There is scarcity of data on the comparative efficacy between bone biopsy drill systems across various types of bone lesions. Our aim was to investigate differences in diagnostic yield, scanning time, and radiation dose between manual and battery-powered bone biopsy systems in CT-guided biopsies of lytic, sclerotic, and infectious bone lesions.MATERIALS AND METHODS: This was a retrospective single-center institutional review board–approved study. A total of 585 CT-guided core needle biopsies were performed at 1 institution from May 2010 to February 2019. Classification of bone lesions, location, bone biopsy system, suspected origin of primary disease, final pathologic diagnosis, diagnostic yield, presence of crush artifacts, radiation dose, and scanning times were collected. For the battery-powered system, OnControl was used. For the manual drill system, Bonopty, Osteo-site, and Laurane drill systems were used. Comparisons in lytic and sclerotic lesions and suspected discitis/osteomyelitis were made using the Fisher exact test. Subgroup analysis of the drill systems for scanning time and radiation dose was performed by 1-way ANOVA.RESULTS: Our patient cohorts consisted of a total of 585 patients with 422 lytic, 110 sclerotic, and 53 suspected infectious lesions. The mean age was 62 ± 13 years with a male/female ratio of 305:280 for all lesions. The diagnostic yield was 85.5% (362/422) for lytic, 82.7% (91/110) for sclerotic, 50.9% (27/53) for infectious lesions, and 82.1% (480/585) for all lesions. No statistical difference was found when comparing diagnostic yields of powered drills with the manual systems for lytic, sclerotic, and infectious lesions. However, in a subgroup analysis, radiation dose and scanning time were significantly lower for powered drill compared with manual drill systems in lytic (P = .001 for both) and sclerotic lesions (P = .028 and P = .012, respectively). No significant differences were seen between the drill systems for suspected infectious lesions.CONCLUSIONS: Our findings demonstrate that there was no statistically significant difference in diagnostic yield when comparing battery-powered and manual bone biopsy systems for CT-guided bone biopsies; however, the use of the power drill system resulted in significantly reduced scanning time and radiation dose in lytic and sclerotic lesions.